Dance learning model for early childhood - Ruiyat, Suci Aprilyati; Sukardjo, Moch.; Solihatin, Etin (Edelweiss Applied Science and Technology, 2024)
Dance education for early childhood is an ability that must be possessed by students as a basis for becoming an educator. The use of a computer-based platform designed to teach theory and practice helps students to better understand the basic material of dance education for early childhood. This research was conducted to design learning media in the form of E-Modules in the course of Dance Education with the target of Early Childhood Education Teacher Education (PGPAUD) students at Setia Budhi University Rangkasbitung. The method used in this research is research and development. Research results from learning design experts, material experts, media experts and linguists. Based on the assessment of the results of the experts, the development of dance art learning for early childhood using E-modules is feasible to use. This can be seen from the results of the T-test which has a significant increase in student learning outcomes after using the E-Module, so it is effective for improving dance skills for early childhood.